ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN WAKTU TUNGGU PASIEN RAWAT JALAN DI PUSKESMAS TLOGOSARI WETAN KOTA SEMARANG MENURUT PERSEPSI PASIEN. - Desi Purwiyanti; Antono Suryoputro; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2019)
Primary health care is a health service facility where organize first-rate individual health care efforts, one of which is outpatient care. Quality outpatient services so as to provide satisfaction to patients. One factors that needs to be considered is patient waiting time. There are still complaints about waiting times, speed of service, service facilities and summoning sources are less still found in the Tlogosari Wetan health center with the category of the number of visits including many but experienced a decrease in visits from the previous year. Objective: Analyze the factors related to the waiting time of outpatients in the Tlogosari Wetan Health Center in Semarang City according to the patient's perception. Method: This research was using quantitative model with with analytical survey approach and cross sectional research design. Samples totaled 100 with accidental sampling. The result data of data was number with Chi-Square test. Result:The data showed that the majority of respondents aged adult, female and high school educated. Most respondents were adults, female and medium educated. The average registration service time is 3.81 min, the main service is 7.6 min, supporting services are 2.36 min. Average registration waiting time is 15.28 min, main service is 23.83 min, supporting service is 11.38 min. Respondents' perceptions of service time, service discipline, service facilities, the source of the call and waiting time are good. Variables related to the perception of outpatients waiting time at the Tlogosari Wetan Health Center in Semarang City included perceptions of service time (p = 0.018), perception of service discipline (p = 0.01), perception of service facilities (p = 0.000). While the variables that are not related include perception of the source of calling (p = 0.280). Suggestion: Print larger and strategically placed online registration information, place reading material to look and add the latest reading material, as well as periodic checks and maintenance of facilities and sources of calling.